2017
DOI: 10.1038/s41598-017-11100-8
|View full text |Cite
|
Sign up to set email alerts
|

Honeycomb-like ZnO Mesoporous Nanowall Arrays Modified with Ag Nanoparticles for Highly Efficient Photocatalytic Activity

Abstract: A new structure of honeycomb-like ZnO mesoporous nanowall arrays (MNWAs) with highly efficient photocatalytic activity was designed and successfully synthesized on Al foil by hydrothermal method. The nanowalls of ZnO-MNWAs have mesopores, which possess a large surface area. The visible light absorption of ZnO-MNWAs was efficiently stronger than ZnO nanowire, resulting in that the photocatalytic activity of ZnO-MNWAs, whose bandgap energy was 3.12 eV, was 5.97 times than that of ZnO nanowires in the degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…Al(OH) 4 − promote the lateral growth of Zn-based nanostructure by binding the Zn 2+ terminated planes and obstructing the growth along the (0001) direction. This is also confirmed by the fact that the growth rate and the quality of ZnO NWLs are affected by the generation rate of Al(OH) 4 − [8,37,38]. Post-annealing processes were demonstrated to convert the as-grown nanowalls in pure ZnO [30].…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Al(OH) 4 − promote the lateral growth of Zn-based nanostructure by binding the Zn 2+ terminated planes and obstructing the growth along the (0001) direction. This is also confirmed by the fact that the growth rate and the quality of ZnO NWLs are affected by the generation rate of Al(OH) 4 − [8,37,38]. Post-annealing processes were demonstrated to convert the as-grown nanowalls in pure ZnO [30].…”
Section: Resultsmentioning
confidence: 63%
“…The layered basic zinc salts (LBZS), for example, are species characterized by a lamellar structure, with high surface area, that, under particular conditions of synthesis [36], represent an intermediate phase of the formation of ZnO in solution. A particular ZnO sheets-like nanostructure is represented by nanowalls [8,30,37,38] that is commonly generated in a zinc salt-based aqueous solution using an Al-covered substrate. It was observed that the Al has a significant role in generating the morphological shape of the nanowalls through the Al(OH) 4…”
Section: Resultsmentioning
confidence: 99%
“…Photocatalysis is becoming an increasingly popular choice for the degradation of pollutants, particularly for wastewater with relatively low concentrations of recalcitrant organic constituents. Photocatalysis offers numerous advantages over alternative techniques; these advantages include total mineralization, which avoids subsequent waste disposal problems; low operating costs; easy accessibility; high performance; and efficient action under ambient environmental conditions [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…(1) (2) Numerous researches have intensively been investigated to overcome these disadvantages and to enhance the photocatalytic activity of ZnO, such as: combining ZnO with other semiconductors [13][14][15], transition metals [16], covering ZnO with a transparent thin film using PANI [17], polysilane [12], or combining with noble metals such as: Ag [18] and Pt [19]. However, there are several limitations due to its wide band gap (>3.2 eV) even with doping material which means that the material can be only active at the ultraviolet region.…”
Section: Introductionmentioning
confidence: 99%